Zur Geschichte des Eigengebrauchs im schweizerischen Urheberrecht - Entwicklung, Erkenntnisse, Quellen - Thouvenin, Florent (sui generis Verlag, 2023)
The regulation of personal use is the most important barrier to Swiss copyright law. It largely frees the use of copyrighted works by private individuals, in the classroom and within companies and other organizations, but provides for remuneration for certain uses. From mere fragments in the first copyright law to today's regulation, the barrier has been continuously expanded. The driving force was technical progress, which made new uses possible, and developments at international level. This booklet traces the historical development, makes the relevant sources available and thus provides the basis for a well-founded historical interpretation of the current regulation.